Macedonian Affective Rhizome: Fear and Shame in the Case of the Macedonian “Name Issue” - Blazheva, Ana (Identities: Journal for Politics, Gender and Culture, 2019)
The text examines two core emotions - fear and shame - and how they shape the affective and social dynamic in relation to the Macedonian “name issue.” Both fear and shame are analyzed through phenomenological approach and in relation to other affects and as core affects that also enable social polarization. Polarization is explained through two Gestalt concepts: polarities and fixed gestalts that serve to analyze the phenomenon that results in exclusionary and divisionary types of thinking and behavior into two blocs - “us” vs “them.” The intersubjectivity is taken to be one of the core conditions of the social field that shape its dynamic as a crucial argument towards the need for overcoming polarized and dichotomized logic of understanding social and political polarization. The analysis shows that fear and shame create a rhizomatic pattern that connects different affects binding together and creating complex structures of behavioral responses and intersubjective space. Enacted through discourse, those affects shape the Macedonian social body as wounded by fear, anxiety, shame, hate, anger and trauma, all of which constitute experience of parlous precarity. Those experiences could not be reduced to binary positions, but they create multiplicity. Author(s): Ana Blazheva Title (English): Macedonian Affective Rhizome: Fear and Shame in the Case of the Macedonian “Name Issue” Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 92-99 Page Count: 8 Citation (English): Ana Blazheva, “Macedonian Affective Rhizome: Fear and Shame in the Case of the Macedonian ‘Name Issue,’” Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019): 92-99.